Adsorption of Thorium(IV) from Aqueous Solution Using Natural Bentonite from Pacitan, Indonesia - Amalia Ekaputri Hidayat; Suci Indryati; Roza Indra Laksmana; Inda Robayani Walayudara; Deden Dharmawan; Rommy; Aditya Widian Putra; Afiq Azfar Pratama; Rachmat Fauzi Hidayat; Saka Wahyu Hidayat (EKSPLORIUM, 2026)
Separating and utilizing thorium from industrial by-products is essential for economic, energy, and environmental reasons. Natural bentonite can be an effective adsorbent for removing various contaminants, including thorium. This study aims to determine the effectiveness of natural bentonite from Pacitan as an adsorbent for thorium removal. Batch adsorption experiments were conducted using a surrogate thorium solution to evaluate the effects of adsorbent dosage, contact time, and adsorption kinetics and isotherms. The study shows that the adsorbent's pHpzc is 7. The adsorbent also shows a cation-exchange capacity of 90.69 meq/100g. The adsorption experiments revealed that using 0.1 g of adsorbent in a 50 mL solution containing 100 ppm thorium yielded an adsorption efficiency of 99.34%. Experimental observations determined an optimum contact time of 120 minutes with 99.80% efficiency. The adsorption data were well-fitted by the pseudo-second-order kinetic model and the Langmuir isotherm, suggesting chemisorption-dominated behavior consistent with monolayer coverage on homogeneous active surface sites. These findings indicate that natural bentonite from Pacitan is a promising, cost-effective material for removing thorium from wastewater.